Tele-echocardiography – Made for astronauts, now in hospitals - M. Balasingam; J. Ebrahim; I.A. Ariffin (Indian Heart Journal, 2017)
Telemedicine, ie ‘the delivery of healthcare and sharing of medical knowledge using telecommunication systems' has penetrated every field of medicine. As a result, tele-echocardiography, the study of the heart via telemedicine started expanding. Ironically, space became the next frontier for mankind's new innovations and technology pursuit. However, the microgravity environment of space is known to be challenging to astronauts hearts. As such, new tele-echocardiography techniques have evolved. The main aim was to research a system that can be operated by a layperson but still be able to provide high yield diagnostic information in real time to specialists on earth. This spin-off space technology is recognized to have a positive impact, especially in developing countries with vast terrain. It is now utilized in hospitals and other terrestial locations where patients in remote regions can have their hearts analysed and data relayed to specialists in bigger centres for interpretation and further management.